การพัฒนาโมเดลความสัมพันธ์เชิงสาเหตุของพฤติกรรมการสูบบุหรี่/ดื่มสุรา ในวัยรุ่น และการศึกษาความไม่แปรเปลี่ยนของโมเดลระหว่างอายุ - สิทธิพงศ์ วัฒนานนท์สกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
To develop and validate the causal models of adolescent smoking/ drinking behaviors, and to examine the invariance of the developed models across age groups. This study was approved by the Ethical Review Committee (ECCU) with the COA No.148/2009. The participants consisted of 2,008 students from 3 age groups, secondary school students, high school students, and university students, recruited from multistage random sampling technique. The developed model consisted of seven latent variables: family functioning, supportive parenting, good self-control, poor self-control, protective factors, risk factors, and smoking and drinking behavior. Data were collected by questionnaires with reliability ranged from .85-.95. Structure equation model (LISREL 8.52) was used for statistical analysis. Structural modeling analyses indicated that: 1. The causal model of smoking and drinking behavior for each age group, secondary school students (Chi-square = 234.974, df = 201, p = .051, GFI = .970, AGFI = .958), high school students (Chi-square = 263.015, df = 227, p=.051, GFI = .966, AGFI = .959), and university students (Chi-square = 129.243, df = 128, p = .453, GFI = .984, AGFI = .964), were best fit to the empirical data. All independent variables in the model accounted for 67.20%, 82.30%, and 67.90% of total variance of smoking and drinking behavior of secondary school students, high school students, and university students, respectively. 2. The three causal models of each age group were invariant for model form. However, the causal effects between latent exogenous variables and latent endogenous variables, as well as the causal effects among endogenous variables, were significantly different across age groups.